Exploring the cecal microbial community associated with fat deposition in sheep and its possible pathways of action - Jiangbo Cheng; Dan Xu; Deyin Zhang; Kai Huang; Yukun Zhang; Xiaolong Li; Yuan Zhao; Liming Zhao; Quanzhong Xu; Xiaobin Yang; Zongwu Ma; Huibin Tian; et al. (Microbiology Spectrum, 2025)
ABSTRACT Fat deposition is a crucial economic trait during sheep growth and development, closely linked to economic returns. Current research on sheep’s digestive tract predominantly focuses on the rumen, but the composition of the cecal microbiota and its relationship with host fat deposition remains largely unexplored. In this study, we sequenced the cecal microbiota of 60 Hu sheep, exhibiting marked differences in traits. The most abundant species in the sheep cecum were Firmicutes and Bacteroidota. Statistical analyses revealed significant differences in microbial community structures among different fat-deposition groups (P < 0.05). Using a random forest regression model and linear regression, 15 microbial biomarkers, including Lachnospiraceae_NK3A20_group, Turicibacter, and Bacteroides, were identified as key contributors to fat deposition. Additionally, volatile fatty acids (VFAs) in the cecum and biochemical indices in serum were measured. Acetic acid was the most abundant VFA in the cecum, while isobutyric acid levels were significantly higher in the low-fat group than in other groups (P < 0.05). Serum triglyceride (TG) levels were significantly higher in the high-fat group (P < 0.05). Correlation analysis revealed a significant association between Lachnospiraceae_NK3A20_group and acetic acid levels, as well as between TG levels and fat deposition traits (P < 0.05). TG levels were negatively correlated with acetic acid concentrations (P < 0.05). These findings suggest that the cecal microbiota influences fat deposition in sheep, potentially via the VFAs-TG metabolic pathway.IMPORTANCECompared with muscle development, fat deposition consumes more energy, and controlling the fat deposition process can effectively reduce energy waste. Current research on rumination mainly focuses on the rumen but lacks research on the hindgut. This study identifies differences in the cecal microbiota of sheep with varying fat deposition levels and highlights significant correlations between specific microorganisms, cecal metabolites, and host traits. Therefore, the regulation of cecal microorganisms can help improve the fat deposition characteristics of sheep.